Nuclear receptors agonists exert opposing effects on the inflammation dependent survival of breast cancer stem cells - Papi, A (Nature Publishing Group, 2012)
Recent literature highlights the importance of pro-inflammatory cytokines in the biology of breast cancer stem cells (CSCs), unraveling differences with respect to their normal counterparts. Expansion of mammospheres (MS) is a valuable tool for the in vitro study of normal and cancer mammary gland stem cells. Here, we expanded MSs from human breast cancer and normal mammary gland tissues, as well from tumorigenic (MCF7) and non-tumorigenic (MCF10) breast cell lines. We observed that agonists for the retinoid X receptor (6-OH-11-O-hydroxyphenanthrene), retinoic acid receptor (all-trans retinoic acid (RA)) and peroxisome proliferator-activated receptor (PPAR)-γ (pioglitazone (PGZ)), reduce the survival of MS generated from breast cancer tissues and MCF7 cells, but not from normal mammary gland or MCF10 cells. This phenomenon is paralleled by the hampering of pro-inflammatory Nuclear Factor-κB (NF-κB)/Interleukin-6 (IL6) axis that is hyperactive in breast cancer-derived MS. The hindrance of such pathway associates with the downregulation of MS regulatory genes (SLUG, Notch3, Jagged1) and with the upregulation of the differentiation markers estrogen receptor-α and keratin18. At variance, the PPARα agonist Wy14643 promotes MS formation, upregulating NF-κB/IL6 axis and MS regulatory genes. These data reveal that nuclear receptors agonists (6-OH-11-O-hydroxyphenanthrene, RA, PGZ) reduce the inflammation dependent survival of breast CSCs and that PPARα agonist Wy14643 exerts opposite effects on this phenotype.